2008
DOI: 10.1038/nmat2102
|View full text |Cite
|
Sign up to set email alerts
|

Morphology evolution via self-organization and lateral and vertical diffusion in polymer:fullerene solar cell blends

Abstract: Control of blend morphology at the microscopic scale is critical for optimizing the power conversion efficiency of plastic solar cells based on blends of conjugated polymer with fullerene derivatives. In the case of bulk heterojunctions of regioregular poly(3-hexylthiophene) (P3HT) and a soluble fullerene derivative ([6,6]-phenyl C61-butyric acid methyl ester, PCBM), both blend morphology and photovoltaic device performance are influenced by various treatments, including choice of solvent, rate of drying, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

64
1,364
4
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,434 publications
(1,437 citation statements)
references
References 42 publications
64
1,364
4
5
Order By: Relevance
“…69 Evidence for spontaneous vertical phase segregation has also been reported in blends of polymers with PCBM. Campoy-Quiles et al 70 showed using spectroscopic ellipsometry that P3HT tends to segregate towards the top of a 1 : 1 blend film of P3HT and PCBM and that this segregation is enhanced following thermal annealing for a blend film on silica. However, replacing the silica substrate with a lower surface energy substrate led to the opposite sense of segregation, with P3HT moving towards the substrate.…”
Section: Blend Compositionmentioning
confidence: 99%
“…69 Evidence for spontaneous vertical phase segregation has also been reported in blends of polymers with PCBM. Campoy-Quiles et al 70 showed using spectroscopic ellipsometry that P3HT tends to segregate towards the top of a 1 : 1 blend film of P3HT and PCBM and that this segregation is enhanced following thermal annealing for a blend film on silica. However, replacing the silica substrate with a lower surface energy substrate led to the opposite sense of segregation, with P3HT moving towards the substrate.…”
Section: Blend Compositionmentioning
confidence: 99%
“…Upon thermal annealing, the difference in the surface energies will influence the concentration of the components at the surface with the lower surface energy component preferentially segregating to surface. 48 This would describe the preannealed film where the electrode is evaporated onto the thin films after thermal annealing. However, for the postannealed film, it is the difference in interfacial energies of the components that is important.…”
Section: Thermal Annealing Approachmentioning
confidence: 99%
“…The DSIMS results have, also, been supported by variable-angle spectroscopy ellipsometry (VASE), X-ray photoelectron spectroscopy (XPS), near-edge Xray absorption fine structure spectroscopy (NEXAFS) and neutron reflectivity (NR) studies in our laboratories and elsewhere. 42,[47][48][49][50][51] It should also be noted that the distribution of components normal to the film surface is also dependent on the nature of the solvent used. 52 The interactions between the conjugated polymer, here P3HT, and PCBM, that is, their miscibility, and the solubility of the components in the solvent use for film preparation are important parameters that must be considered in describing and controlling the morphology of the resultant active layer.…”
Section: Thermal Annealing Approachmentioning
confidence: 99%
“…One option to modify the photovoltaic parameters and the morphology of bulk heterojunction solar cells distinctly, is ternary blending of three components, either two polymers and one fullerene or one polymer and two fullerenes 31, 68, 69, 70, 71. In the presented study ternary blends of semicrystalline AnE‐PV ab (anthracene‐containing poly(p‐phenylene‐ethynylene)‐alt‐poly(p‐phenylene‐vinylene) (PPE‐PPV) copolymers (AnE‐PV), equipped with octyloxy side‐chains at the PPE‐part and 2‐ethylhexyloxy side‐chains at the PPV‐part) and amorphous AnE‐PV ba (AnE‐PV equipped with 2‐ethylhexyloxy side‐chains at the PPE‐part and octyloxy side‐chains at the PPV‐part)—both structures may be found in the Supporting Information—in various ratios were applied to create those different interfaces as mentioned above 33, 34, 72, 73.…”
Section: Introductionmentioning
confidence: 99%